Kompleksitas Otonomi Daerah Dan Gagasan Negara Federal Dalam Negara Kesatuan Republik Indonesia - Ni matul Huda; Despan Heryansyah (Jurnal Hukum IUS QUIA IUSTUM, 2019)
The 1998 reforms opened a new discourse on the direction of the Indonesian constitutional system. There were six aspects that became the demand for the reform at the time, one of which was the rearrangement of central and regional relations, by bestowing autonomy to the regions to the broadest extent possible. In relation to this particular issue, the formulation of the problems in this paper is as follow: first, how is the complexity of the problem of regional autonomy in Indonesia, especially in terms of authority? Second, what are the implications of the complexity of the problem for the existence of the Unitary Republic of Indonesia. The method used in this research is juridical normative, where the focus of data collection and exploration is through literature study and supported by interviews. This study concludes, firstly, the complexity of the problem of regional autonomy is triggered by, among others, the efforts of decentralization in the Regional Government Law after reform. Whereas Indonesia with a very broad cultural background and regional reality, is more suitable to be managed in the form of an expanded asymmetric decentralization model. Secondly, if the relationship between the central government and the regions is managed centrally it has the potential to cause resistance from the regions, it can threaten the existence of the Republic of Indonesia.